1996
DOI: 10.2307/1382721
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Growth and Age Estimation in the Indian Pygmy Bat Pipistrellus mimus

Abstract: The Indian pygmy bat Pipistrellus mimus produced two young per litter, which were altricial at birth. Empirical growth curves were derived by measuring length of forearm, body mass, and length of the total gap of the fourth metacarpal-phalangeal joint. Length of forearm and body mass followed a linear pattern of growth until day 20 and subsequently reached stability. The length of the total gap of the metacarpal-phalangeal joint showed a linear increase up to 20 days, followed by a linear decrease until ca. 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
(17 reference statements)
0
21
1
Order By: Relevance
“…Efforts to analyse the age of individuals subsequent to linear growth have been fraught with practical and analytical dif®culties (Kunz & Stern, 1995). Use of linear equations derived from lengths of forearm and epiphyseal gap from known-age bats (Kunz & Anthony, 1982;Burnett & Kunz, 1982;de Paz, 1986;Isaac & Marimuthu, 1996) extends the age at which age prediction is possible. This, in turn, facilitates analyses of relationships between pup age and developmental variables such as the ontogeny of¯ight and foraging (Powers et al, 1991;Stern, Kunz & Bhatt, 1997), echolocation (Moss et al, 1997), mineral accretion (Studier & Kunz, 1995;Papadimitriou et al, 1996), and milk composition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to analyse the age of individuals subsequent to linear growth have been fraught with practical and analytical dif®culties (Kunz & Stern, 1995). Use of linear equations derived from lengths of forearm and epiphyseal gap from known-age bats (Kunz & Anthony, 1982;Burnett & Kunz, 1982;de Paz, 1986;Isaac & Marimuthu, 1996) extends the age at which age prediction is possible. This, in turn, facilitates analyses of relationships between pup age and developmental variables such as the ontogeny of¯ight and foraging (Powers et al, 1991;Stern, Kunz & Bhatt, 1997), echolocation (Moss et al, 1997), mineral accretion (Studier & Kunz, 1995;Papadimitriou et al, 1996), and milk composition .…”
Section: Discussionmentioning
confidence: 99%
“…Kunz & Anthony (1982) described a method for quantifying post-natal growth rates in bats based on linear changes in the length of the forearm and metacarpal-phalangeal epiphyseal cartilages (= epiphyseal plates). This method has made it possible to extend the period of reliable age prediction from two to four weeks in Myotis lucifugus (Kunz & Anthony, 1982), from three to six weeks in Eptesicus fuscus (Burnett & Kunz, 1982), Myotis myotis (de Paz, 1986), and Tadarida brasiliensis , and from three to seven weeks in Pipistrellus mimus (Isaac & Marimuthu, 1996). Agepredictive equations derived from these linear changes also make it possible to quantify age-related differences in such variables as wing morphology and ontogeny of ight (Powers, Kandarian & Kunz, 1991;Stern, Kunz & Bhatt, 1997), mineral accretion (Studier & Kunz, 1995;Papadimitriou, Swartz & Kunz, 1996), nightly emergence behaviour (Kunz & Anthony, 1996), ontogeny of echolocation (Moss et al, 1997), and milk composition .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the length of total epiphyseal gap can be used as soon as the secondary centre of ossification formed and the epiphyseal gap begins to decrease linearly (after 15 days in C. sphinx). The values of linear increase in the forearm length and linear decrease in the total epiphyseal gap are used to derive equations for estimating the age of young bats in several studies (e.g., Kunz and Anthony, 1982;De Paz, 1986;Isaac and Marimuthu, 1996;Rajan and Marimuthu, 1999;Baptista et al, 2000;Cheng and Lee, 2002). Our analysis of postnatal growth based on three models showed that the logistic and Gompertz models best described the growth patterns of length of forearm and body mass of C. sphinx, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Most of the studies carried out so far on postnatal development and age estimation have been restricted mainly to microchiropterans; for example on Vespertilionidae (e.g., Krátký, 1981;De Fanis and Jones, 1995;Hughes et al, 1995;Isaac and Marimuthu, 1996;Hoying and Kunz, 1998;Swift, 2001), Molossidae , Phyllostomidae (Stern and Kunz, 1998), Megadermatidae (Rajan and Marimuthu, 1999) and Hipposideridae (Cheng and Lee, 2002). Studies on growth aspects in megachiropterans are much limited (Kunz and Stern, 1995;Kunz and Hood, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…According to Kurta and Kunz (1987) and Hayssen and Kunz (1996), the body mass of a single pup may vary from 20% to 40% of a female's post-partum mass. However, a relative mass as low as 16.6% has also been reported for Pipistrellus mimus (Isaac & Marimuthu, 1996).…”
Section: Discussionmentioning
confidence: 93%